Vaccination against tick-borne encephalitis virus in Denmark, Norway and Sweden - Mette F. Hansen; John Shorter; Martin T. Jepsen; Anders Boman; Pikka Jokelainen; Solveig Jore; Daniel Slunge; Karen A. Krogfelt (Vaccine: X)
Tick-borne encephalitis (TBE) is one of the more severe and widespread arboviral infections in Europe, with an increase in incidence over the past decades in several countries. Prevention strategies against infection with the virus include vaccination and protection against tick bites. The virus is typically found in very localized endemic areas known as microfoci, possibly affecting differences in public knowledge and vaccination strategies between countries and regions. This study investigated how self-reported TBE vaccination status is associated with demographic variables, knowledge of TBE, and tick and TBE virus exposure in Denmark, Norway, and Sweden. An online questionnaire with 48 questions, including demographic prompts, knowledge questions about TBE, and TBE vaccination status was sent out to respondents in the three countries. The overall proportion of reportedly TBE-vaccinated people in the three countries (N = 2668) was 13 %, but with large differences between countries. The proportion was 28.5 % in Sweden (N = 1096), 2.3 % in Norway (N = 789) and 2.2 % in Denmark (N = 783), corresponding well with the higher TBE incidence in Sweden. The reported TBE-vaccination rates in Denmark and Norway were too low for further analyses. The results from Sweden were analysed by logistic regression, showing that respondents in Sweden who reportedly visited TBE virus risk areas were more likely to be vaccinated. The general knowledge of TBE appeared to be limited, especially in Denmark and Norway.